Association between disability pension, nutritional condition and physical inactivity in adults from a middle-size Brazilian City - Araujo, Monique Yndawe Castanho [UNESP]; Cantarutti, Débora Christante [UNESP]; Queiroz, Dayane Cristina [UNESP]; Turi, Bruna Camilo [UNESP]; Christofaro, Diego Giuliano Destro [UNESP]; Codogno, Jamile Sanches [UNESP] (Universidade Estadual de Maringa, 2016)
To analyze the occurrence of disability pension and its association with physical inactivity and nutritional condition, isolated and aggregated way, in Brazilian National Health System patients aged ≥50 years-old, in 2013. 542 adults of both sexes, with a mean age of 61.9 years (95% CI = 61.2, 62.7) were evaluated in two Basic Health Units. Body mass index (kg/m2) was calculated and disability pensions, habitual physical activity and presence of diseases were self-reported. Variable cluster of physical inactivity and obesity was created with the aim to analyze together physical activity and nutritional status. In overall sample, the occurrence of disability pension was 25.6% (95%CI= 21.9%-29.3%), which it was associated with cluster of obesity and physical inactivity (OR= 2.26 [95%CI: 1.14; 4.47]) when model was adjusted for heart attack, osteoporosis, arthritis/arthrosis, disc herniation and low back pain. It is concluded that the occurrence of disability pension was higher than 25% and significantly related to cluster of obesity and physical inactivity.
Keywords: Obesity; Pensions; Unified health system